COMMUNITY PARTNERSHIP PROGRAM TO PREVENT STUNTING IN TODDLER THROUGH CADER EMPOWERMENT - Yulidaningsih, Elok; Tunik, Tunik; Mandasari, Yuyun Putri (SYNTIFIC, 2024)
Background. Stunting is a condition of failure to thrive in children under five (babies under five years) which is caused by chronic malnutrition so that the child is too short for his age. Malnutrition occurs when the baby is in the womb and in the early days after the baby is born, but stunting only appears after the baby is 2 years old. Stunting can be caused by not going through the golden period which begins in the first 1000 days of life, which is the formation of a child's growth and development in the first 1000 days. Based on data obtained from the Suruh Community Health Center, stunting incidents were still found in the Suruh Community Health Center area. The results of the Suruh Community Health Center survey show that the factors that cause stunting in the Suruh Community Health Center work area are economic factors and parenting patterns. The stunting process is actually chronic. In overcoming stunting, all sectors and levels of society need to play a role.Research Method. This community service method is pre and post tests, counseling about early detection of stunting to cadres, training (training on how to measure anthropometry and development in children) to cadres, and distribution of anthropometric measuring equipment to cadres. The number of cadres targeted in this community service activity is 25 cadres from several villages in the Suruh Community Health Center working area. Findings. The results of community service based on observation and evaluation are an increase in cadres' knowledge about early detection of stunting, and cadres have skills in carrying out anthropometric measurements.Conclusion. Community service in the form of training and counseling carried out in the Suruh Community Health Center area generally provides benefits to cadres, mothers of toddlers and the community. Cadres have the motivation to provide information to other cadres and mothers of toddlers to prevent stunting, and are willing to carry out appropriate anthropometric measurements for toddlers at posyandu